Still a superwoman? How female academics from the former Soviet Union negotiate work-family balance abroad - Antoshchuk, Irina A; Gevinner, Irina (Monitoring Obshchestvennogo Mneniya: Ekonomicheskie i Sotsial'nye Peremeny, 2020)
Since the 1930s, a peculiar 'working mother' gender contract was dominant in the Soviet Union formally empowering women. The pressing expectation of this contract and a necessity to combine motherhood, housework and employment led to the image of the near superwoman who 'has it all'. This paper examines whether highly-skilled Russian-speaking female academics continue to adhere to this cultural ideal striving for work-life balance after migration to the UK and Germany. Based on qualitative interviews with 22 female scholars, the article provides a typology of scenarios for negotiating professional and private life. It elaborates on how role-related partners contribute to achieving balance between paid employment and mothering and explores the consequences for women's well-being. Moreover, the study suggests a feminist approach to analyzing work-family balance, which valorises women's point of view, emphasizing motherhood, children and family relations as an essential personal and social value, while also documenting the increasing challenges faced in the realization of these life priorities. © 2020 Russian Public Opinion Research Center, VCIOM. All rights reserved.
Keywords: 2000 à aujourd'hui; 2010-2019; allemagne; asie; charge mentale; conciliation famille-travail; discipline; europe; ex-URSS; famille; femmes* russophones; projet charge mentale; périodes historiques; ressource en ligne; royaume-uni; russie; régions géographiques; sciences humaines; sociologie; thématiques; travail

The missing doctors — An analysis of educated women and female domesticity in Pakistan - Mohsin, Mariam; Syed, Jawad (Gender, Work and Organization, 2020)
While the percentage of female students in medical schools in Pakistan is as high as 80–85 per cent, the percentage of female doctors in the medical workforce remains below 50 per cent. Our findings draw on in-depth interviews with 31 female doctors to show that the reasons behind the gap between female medical students and female medical professionals are multifold and multilayered, ranging from individual reasons to organizational and sociocultural reasons. We use an adapted version of the relational framework developed by Syed and Özbilgin in 2009 to offer a contextual and multilevel understanding of female domesticity in Pakistan. The study suggests that the problem of female doctors dropping out of the medical workforce is a reflection of the interplay of social, organizational and individual factors, which are tied together by social norms. Practical implications suggest that making hospitals and health organizations more inclusive of women and their needs could be a starting point for policymakers to address the gender gap in the medical profession. © 2020 John Wiley & Sons Ltd
Keywords: 2000 à aujourd'hui; 2010-2019; asie; conciliation famille-travail; famille; femmes* médecins; maternité; pakistan; projet charge mentale; périodes historiques; régions géographiques; thématiques; travail

Labor market outcomes of professional women with two children after the one‐child policy in China - Shen, Yang; Lai, Jiang (The Journal of Social Issues, 2020)
Since the implementation of the two‐child policy in China in 2016, it is unclear how professional women's labor force outcomes and family commitments have changed. Using interviews with 26 professional women with two children in Shanghai, we examined their work–life transitions and labor market outcomes. We found that the overarching constraints the interviewees faced included a lack of institutional childcare support, low paternal participation and increased physical and cognitive childcare labor. The women also experienced different constraining and enabling factors, leading to four types of labor market outcomes: enhancement, rebound, interruption and stagnation. Most of the interviewees who experienced career upward mobility after giving birth to a second child were urban singleton daughters who received tremendous parental support. Some participants experienced career interruption due to a lack of social support. The state should ensure family‐friendly work environments and promote paternal participation to reduce women's work–life conflict and address gender inequality.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asie; chine; conciliation famille-travail; famille; inégalités hommes-femmes; maternité; projet charge mentale; périodes historiques; rapports sociaux de sexe; régions géographiques; sexisme; soutien familial; systèmes d'oppressions; thématiques; travail; travail reproductif; travail rémunéré

Benefits and constraints of the agricultural land acquisition for urbanization for household gender equality in affected rural communes: A case study in Huong Thuy Town, Thua Thien Hue Province, Vietnam - Thi, Nhung Pham; Kappas, Martin; Wyss, Daniel (Land, 2020)
Le gouvernement vietnamien a mis en œuvre l'acquisition de terres agricoles pour l'urbanisation (ALAFU) depuis 2010, ce qui a provoqué un niveau élevé de transition socio-économique dans le pays. Dans cet article, nous avons appliqué l'approche genre et développement pour découvrir comment l'ALAFU a influencé l'égalité des sexes au sein des ménages dans les zones touchées de la province de Thua Thien Hue, au Vietnam. Les données de cet article ont été principalement collectées à partir de deux enquêtes auprès de groupes de ménages, de quatre discussions de groupe et de six entretiens avec des informateurs clés. Le groupe 1 couvre 50 ménages affectés dont les terres agricoles ont été acquises pour l'urbanisation, tandis que le groupe 2 se compose de 50 ménages dont les terres agricoles n'ont pas été confisquées. Les résultats révèlent que l'ALAFU a conduit à un accès réduit aux terres agricoles pour le groupe 1, mais a contribué à une augmentation du statut économique des femmes des deux groupes en créant des opportunités d'emploi non agricoles avec un bon revenu. Cependant, la plupart de leurs nouveaux emplois sont encore informels, comportent des risques potentiels et la charge de travail de soins non rémunérés est lourde. De plus, bien que le taux de participation des femmes à la prise de décision au sein du ménage ait augmenté, la qualité de la participation est limitée. Leur participation aux activités sociales et aux cours de formation professionnelle s’est améliorée de manière insignifiante. Par conséquent, si le Gouvernement continue de promouvoir l’ALAFU, il devra prendre en compte les inégalités structurelles entre les sexes pour atteindre ses objectifs de développement durable.
Number: 8
Keywords: 2000 à aujourd'hui; 2010-2019; asie; care; participation citoyenne des femmes; projet charge mentale; périodes historiques; régions géographiques; terres agricoles; thématiques; travail; travail du care; urbanisation; vietnam

Hindu nation and its queers: Caste, islamophobia, and de/coloniality in India - Upadhyay, Nishant (Interventions: international journal of postcolonial studies, 2020)
Le jugement de la Cour suprême indienne de 2018 dépénalisant l'homosexualité a été qualifié d'"acte décolonial". Article 377, qui criminalisait l'homosexualité, était une loi coloniale introduite par les Britanniques en Inde, que l'État postcolonial a maintenue jusqu'en 2018. Le jugement peut être « décolonial » dans son intention, mais il y a d'autres processus simultanés en jeu qui ne sont pas si décoloniaux dans la pratique ; cet essai soutient que ces processus sont le colonialisme, la suprématie brahmanique et l'islamophobie. La violence basée sur la caste fait partie intégrante de l'hindouisme et est étroitement liée à d'autres matrices d'oppression, faisant de la caste le fondement de toute revendication de l'hindouisme en tant que queer, trans et non conforme au genre amical. Étudiant les récentes réponses nationalistes hindoues en faveur de la dépénalisation de l'homosexualité en Inde, cet essai retrace comment la droite hindoue déploie la queerness pour propager ses agendas islamophobes, castistes et homohindunationalistes. L'essai défend la décolonisation du droit, de l'État.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asie; cours; discours dominant; fem3400; inde; islamophobie; premier cycle; périodes historiques; queer; racisme; ressource en ligne; régions géographiques; sexualité; système colonial; systèmes d'oppressions; thématiques; violences

Work-family balance and the subjective well-being of rural women in Sichuan, China - Yue Shui; Xu, Dingde; Liu, Yi; Liu, Shaoquan (BMC Women's Health, 2020)
Background Due to the great burden of family and the conflicts among family, society and career roles resulting from migrant working, rural women suffer more conflicts between work and family and need more social attention. Previous studies of the conflicts between family and work mainly focus on the group of career women, and there is a lack of the research on the conflicts between work and family of rural women, which needs to be systematically and further studied.Methods This study used a sample survey of 380 rural women in rural areas of Sichuan Province to measure rural women’s cognition of work-family, coordination and handling of conflicts, post-conflict choices, and subjective well-being; the study constructs an ordered multi-class logistic regression model to explore the impact of work-family conflict on the subjective well-being of rural women in rural regions.Results The study result shows that: (1) The level of subjective well-being of rural women is generally high, and 70% of women feel satisfied or very satisfied. (2) The factor which impacts the subjective well-being among rural women most is work-interfering-with-family conflict, followed by work-family balance and confidence in conflict coordination.Conclusion This study can enhance our understanding of rural women in rural areas, and provide a reference for formulating policies to improve people’s life satisfaction.
Keywords: 2000 à aujourd'hui; 2010-2019; asie; bien-être psychosocial; chine; conciliation famille-travail; famille; femmes rurales; projet charge mentale; périodes historiques; régions géographiques; thématiques; travail